2009
DOI: 10.1007/s11064-009-9920-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Resveratrol against Kainate-induced Temporal Lobe Epilepsy in Rats

Abstract: Resveratrol (Res) is a phytoalexin produced naturally by several plants, which has multi functional effects such as neuroprotection, anti-inflammatory, and anti-cancer. The present study was to evaluate a possible anti-epileptic effect of Res against kainate-induced temporal lobe epilepsy (TLE) in rat. We performed behavior monitoring, intracranial electroencepholography (IEEG) recording, histological analysis, and Western blotting to evaluate the anti-epilepsy effect of Res in kainate-induced epileptic rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(87 citation statements)
references
References 37 publications
6
80
0
1
Order By: Relevance
“…In this study, a massive neuronal loss was found in the CA1, CA3 and hilar regions in the kainate group. Furthermore, typical aberrant mossy fibers invading into the granule cell layer and granule cell inner molecular layer in the hippocampus of these rats were noticed, which was consistent with previous studies (Wu et al, 2009) Severe reduction in the number of neurons in the hilar region and neuronal dispersion in the upper blade (white arrow) were observed in the kainate group, but no such marked changes were prominent in the curcumin-pretreated kainate group. *p50.05, **p50.01, ***p50.005 (in comparison with sham); #p50.05, ##p50.005 (in comparison with kainate) (n ¼ 4-5).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, a massive neuronal loss was found in the CA1, CA3 and hilar regions in the kainate group. Furthermore, typical aberrant mossy fibers invading into the granule cell layer and granule cell inner molecular layer in the hippocampus of these rats were noticed, which was consistent with previous studies (Wu et al, 2009) Severe reduction in the number of neurons in the hilar region and neuronal dispersion in the upper blade (white arrow) were observed in the kainate group, but no such marked changes were prominent in the curcumin-pretreated kainate group. *p50.05, **p50.01, ***p50.005 (in comparison with sham); #p50.05, ##p50.005 (in comparison with kainate) (n ¼ 4-5).…”
Section: Discussionsupporting
confidence: 91%
“…The sections were then dehydrated and cover slipped. Assessment of MFS (as Timm index) was obtained from the absolute value of the area of Timm granules divided by the length of DG (Wu et al, 2009). The Timm index for each animal was the mean of three sections.…”
Section: Histological Studiesmentioning
confidence: 99%
“…The incidence and rate of spontaneous seizures was markedly reduced in the resveratrol treatment group. The effect on seizures was associated with neuroprotection in the hippocampus, as well as a reduction in mossy fiber sprouting [101]. These promising results were not fully confirmed in a more recent study of younger kainate-treated rats [102], so that, at present, the potential of resveratrol for disease modification in epilepsy is uncertain.…”
Section: Resveratrolmentioning
confidence: 92%
“…Some, but not all, recent experimental studies also suggest that resveratrol may have utility in epilepsy [100]. Wu et al [101] examined the effects of resveratrol treatment on the occurrence of spontaneous seizures following SE induced by intrahippocampal kainate injection in rats. The incidence and rate of spontaneous seizures was markedly reduced in the resveratrol treatment group.…”
Section: Resveratrolmentioning
confidence: 99%
“…Res or trans-Res has a neuroprotective effect against KA-induced convulsions and the attenuation of raised malondialdehyde levels, and markedly decreases spontaneous seizure frequency, suggesting that Res may be a potential anti-epilepsy agent, at least as an adjunct treatment in KA-induced epilepsy animal models [32,33]. The chronic administration of Res significantly protects against KA-induced damage in the rat hippocampus and olfactory cortex, whereas the same treatment with Res does not play a protective role in an ex vivo hippocampal ischemia model [34].…”
Section: Res-mediated Neuroprotective Effect Against Glu-induced Excimentioning
confidence: 99%